Ping Heng = THE DICHOTOMY OF LEADERSHIP : Dazao chaoji tuandui de er yuan lingdao li fa ze - Willink, Jocko; Babin, Leif; Wang, Xue (Beijing, China : Timeschinese Press, 2020)
Through 12 real battlefield stories and 20 classic management cases, this book helps readers get rid of the trap of leadership perception, accurately control leadership, and achieve leadership through the balance between "team", "task" and "individual" A leap in effectiveness.
Text in simplified Chinese scripts.
Keywords: Leaderships